Barriers to community development in distressed cities: A case study of Camden, New Jersey. Issue 4 (8th July 2016) - Wheeler, Christopher A.
Abstract: Community development theory provides a strong and robust theoretical basis for effective community development practice. However these theoretical constructs have broad implications beyond effective community development practice, they might also inform the lack of community development progress in certain contexts. This article engages community development theory to describe what factors block the advancement of community development in distressed city contexts. By examining the effects of structure, shared meaning, solidarity, agency, and poverty on community development in the case of the city of Camden, New Jersey, the article demonstrates how these social phenomena can potentially inhibit community development progress. The article concludes with a discussion of how these barriers might be overcome to facilitate successful community development.